Adalimumab: 8 years of experience in rheumatoid arthritis. (April 2013) - Tayar, Jean H; Lopez-Olivo, Maria A; Suarez-Almazor, Maria E
Rheumatoid arthritis is the most common autoimmune inflammatory arthritis. TNF-α has a pivotal role in its pathogenesis. Adalimumab was the first fully human antibody against TNF-α to be approved for active rheumatoid arthritis. Its pharmacological characteristics, clinical efficacy, effectiveness and safety are discussed in this article. Based on the summarized studies, adalimumab was shown to be effective in patients with active disease. Its beneficial effect can start as early as 1 week after the first dose, and be maintained in responders for up to 5 years. Adalimumab is generally well tolerated. The most common adverse event is injection site reactions. There is no increased rate of serious adverse events in trials, but serious infections, such as tuberculosis, have been reported in larger observational studies and remain a concern to screen and watch for.